Penyuluhan Pengaruh Minyak Jelantah dan Pelatihan Pemeriksaan Kadar Kimia Darah di Desa Keutapang, Syamtalira Aron - Z, Khairunnisa; Mellaratna, Wizar Putri; Sofia, Rizka; Rahmayani, Sarah; Vidella, Eva; Verza, Meuthia (Auxilium : Jurnal Pengabdian Kesehatan, 2024)
Waste cooking oil is oil derived from plants such as corn oil, vegetable oil, and ghee which has been used as cooking oil and is usually reused for economic reasons. However, when viewed from its chemical composition, used cooking oil contains carcinogenic compounds which occurs during the frying process. The use of used cooking oil can disrupt the body's hemostasis, it can cause many disorders, can increase cholesterol, blood sugar, and uric acid, and can even damage organs. Knowledge about the effects of used cooking oil is expected to be able to change people's lifestyles so that they no longer use used cooking oil. Training on blood chemistry examinations related to cholesterol, uric acid, and blood sugar levels by Cadres in Keutapang Village can help the community and health workers in Keutapang Village as an initial screening to prevent systemic diseases. This activity aims to increase public knowledge regarding the influence of used cooking oil and cadres in Keutapang Village to be able to independently carry out blood chemistry checks for cholesterol, uric acid, and blood sugar levels.